The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1073/pnas.1619573114
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic evolution and the self-organization of ecosystems

Abstract: Metabolism mediates the flow of matter and energy through the biosphere. We examined how metabolic evolution shapes ecosystems by reconstructing it in the globally abundant oceanic phytoplankter Prochlorococcus. To understand what drove observed evolutionary patterns, we interpreted them in the context of its population dynamics, growth rate, and light adaptation, and the size and macromolecular and elemental composition of cells. This multilevel view suggests that, over the course of evolution, there was a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
169
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(179 citation statements)
references
References 158 publications
(203 reference statements)
4
169
0
1
Order By: Relevance
“…Recent molecular clock analyses have suggested that genome streamlining in Prochlorococcus occurred during the Neoproterozoic (500–1000 MYA), well after the Great Oxidation Event of ∼ 2.4 billion years ago, followed by the further differentiation of modern Prochlorococcus ecotypes during the Phanerozoic. (Sánchez‐Baracaldo ; Braakman et al ). Despite rising atmospheric O 2 levels during this time, the oceans were not uniformly oxygenated (Sperling et al ), which probably maintained large cobalt sources from anoxic sediments, as observed in the modern ocean (Hawco et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent molecular clock analyses have suggested that genome streamlining in Prochlorococcus occurred during the Neoproterozoic (500–1000 MYA), well after the Great Oxidation Event of ∼ 2.4 billion years ago, followed by the further differentiation of modern Prochlorococcus ecotypes during the Phanerozoic. (Sánchez‐Baracaldo ; Braakman et al ). Despite rising atmospheric O 2 levels during this time, the oceans were not uniformly oxygenated (Sperling et al ), which probably maintained large cobalt sources from anoxic sediments, as observed in the modern ocean (Hawco et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Cultures growing at high Ni 0 held higher Ni quotas and experienced longer lag phases prior to exponential growth. While it is difficult to evaluate if higher Ni quotas reflect increases in intracellular or periplasmic Ni, the cbiK cobaltochelatase enzyme also has a strong affinity for Ni and is used by some organisms in the biosynthesis of the Ni containing tetrapyrrole F430 (Brindley et al 2003;Moore et al 2017). It is possible that this long lag phase is needed to upregulate Nibinding proteins to decrease competition with cobalt at the binding site of cbiK.…”
Section: Metal Competition In Prochlorococcus Cobalt Uptakementioning
confidence: 99%
“…DOM can exit microbial cells and enter the DOM pool in several ways: sloppy feeding by grazers, lysis by virus, 'spontaneous' (i.e., abiotic-induced) cell lysis, excretion from live cells, and release of membrane vesicles (Nagata and Kirchman, 1991;Ankrah et al, 2014;Biller et al, 2014). Studies thus far indicate that Prochlorococcus can release significant amounts of DOM via excretion and vesicle formation (Bertilsson et al, 2005;Becker et al, 2014;Biller et al, 2014;Braakman et al, 2017), and this release may constitute a significant return on the investment for the HOOH-consuming heterotrophic bacteria. Studies thus far indicate that Prochlorococcus can release significant amounts of DOM via excretion and vesicle formation (Bertilsson et al, 2005;Becker et al, 2014;Biller et al, 2014;Braakman et al, 2017), and this release may constitute a significant return on the investment for the HOOH-consuming heterotrophic bacteria.…”
Section: Evidence For Help In the Oceanmentioning
confidence: 99%
“…If niche selection of genomes adapted to different niches in the water column plays a role, it is most likely to occur in the stable pycnocline where populations remain segregated over longer periods (weeks to month, or longer). Light intensity is not the only, or even the major defining difference between the periodically mixed-layer and the stable pycnocline (Braakman et al, 2017). Compared to the mixed-layer zone, the pycnocline has higher nutrient concentrations with a different composition .…”
Section: Irradiance In a Dynamic Environmentmentioning
confidence: 99%